Physical Mechanisms Controlling the Strength-Deformation Behavior of Frozen Sand: I - Andersen, Glen R.; Germaine, John T.; Ladd, Charles C.; Swan, Chris W. (1992)
A high-pressure low-temperature triaxial compression testing system with on specimen axial strain measurements and lubricated end plattens was developed in order to measure the stress-strain-volume change behavior of frozen Manchester Fine Sand (MFS) from very small (0.01%) to very large (25%) axial strains. The main testing program was conducted at a temperature of T=-9.5 deg C and varied the relative density from 20 to 100%, the confining pressure from 0.1 to 10 MPa, and the strain rate from 0.000003/sec (slow) to 0.0004/sec (fast). These data show a constant Young's modulus that can be explained in terms of a composite materials model; provide the first detailed evaluation of the upper yield stress, which is essentially independent of sand density and confining pressure, and has a rate sensitivity similar to that of granular ice; and show that the peak strength generally increases linearly with sand density, increases nonlinearly with confinement, and has a rate sensitivity much less than granular ice. Initial tests at different temperatures indicate a larger temperature sensitivity than predicted for granular ice. A similar triaxial system was used to measure the stress-strain behavior of unfrozen MFS as a function of relative density and confining pressure. These data are used to evaluate Ladanyi's dilatancy-hardening model developed to predict the strength of frozen sand.